A Method for Rapid Evaluation of Thermal Performance of Wall Assemblies Based on Geographical Location - Jan Kočí; Václav Kočí; Robert Černý (Energies, 2019)
In this study, we present a method for the rapid evaluation of thermal performance of building envelopes without the need of using sophisticated and time-consuming computational modeling. The proposed approach is based on the prediction of monthly energy balances per unit area of a wall assembly using monthly averages of temperature and relative humidity, as well as the elevation of a building’s location. Contrary to most other methods, the obtained results include how moisture content in the wall effects its thermal performance. The developed formulas for calculation of monthly energy balances are verified for nine commonly used wall assemblies in Central Europe in 10 randomly selected locations. The observed agreement of the predicated data was determined using advanced finite-element simulation tools and hourly climatic data, which makes for good prerequisites for the further application of the method in both research and building practices.